2018
DOI: 10.1016/j.jmatprotec.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oil-in-water based nanolubricant containing TiO2 nanoparticles in hot rolling of 304 stainless steel

Abstract: Energy saving and improvement of product quality are of crucial importance in hot rolling of 304 stainless steel. In this paper, oil-in-water (O/W) based nanolubricants containing TiO 2 nanoparticles were developed to reduce the rolling force and improve the surface quality of rolled 304 stainless steel product. Practical hot rolling tests with and without application of lubricant were conducted to systematically investigate the effects of the developed O/W based nanolubricants on the rolling force, surface ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Nevertheless, it is seen that the rolling forces rebounded and increased from 4.75 kN to 4.87 kN, while the fraction of TiO 2 nanoparticles further increased from 3.0 wt.% to 9.0 wt.%. This phenomenon can be attributed to the aggregation of excessive nanoparticles that concentrates at contact regions during rolling processes [ 18 ]. The aggregation of TiO 2 nanoparticles leads to aggravated rubbing and thereby gives a rise to the COF (Friction Coefficient), causing more energy consumption induced by friction and thus enhancing the rolling force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is seen that the rolling forces rebounded and increased from 4.75 kN to 4.87 kN, while the fraction of TiO 2 nanoparticles further increased from 3.0 wt.% to 9.0 wt.%. This phenomenon can be attributed to the aggregation of excessive nanoparticles that concentrates at contact regions during rolling processes [ 18 ]. The aggregation of TiO 2 nanoparticles leads to aggravated rubbing and thereby gives a rise to the COF (Friction Coefficient), causing more energy consumption induced by friction and thus enhancing the rolling force.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that refined tribological behaviour can be achieved by the nano-TiO 2 lubricating fluid. Xia et al [ 18 ] developed oil-in-water-based nanolubricants containing TiO 2 nanoparticles and found that the lubrication effects can be attributed to the nanoparticles that entered the deform zone. Wu et al [ 19 , 20 ] performed a series of hot rolling tests of microalloyed steel and low-alloy steel under different lubrication conditions, and found that an optimal fraction of 4.0 wt.% TiO 2 nanoparticles demonstrates the best lubrication performance.…”
Section: Introductionmentioning
confidence: 99%
“…Lubricants, such as neat oils [2][3][4] and oil-in-water emulsions [5,6], have been extensively used to reduce the friction and wear, and satisfactory results have been obtained. To further enhance the friction-reduction and anti-wear properties of the oil-containing lubricants, great efforts have been directed towards incorporating different types of nanoadditives into the base lubricants [7][8][9]. These nanoadditives include metals, metal oxides, metal sulphides, non-metallic oxides, carbon materials, composites, and others such as nitrides [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sharif et al [26] used SiO2 PAG nanolubricant in the ventilation system of an automobile. Another application of nano-lubricant is in cooling for the rolling procedure or machining process which mostly water-based nanofluid is used [27][28]. Obviously, desired thermal distribution and enhanced heat transfer are crucial in these processes.…”
Section: Introductionmentioning
confidence: 99%